Prognostic Significance and Biologic Associations of Senescence‐Associated Secretory Phenotype Biomarkers in Heart Failure - Salman, Oday; Zamani, Payman; Zhao, Lei; Dib, Marie Joe; Gan, Sushrima; Azzo, Joe David; Pourmussa, Bianca; Richards, Arthur Mark; Javaheri, Ali; Mann, Douglas L.; Rietzschel, Ernst; Zhao, Manyun; et al. (Journal of the American Heart Association, 2024)
The role of cellular senescence in human heart failure (HF) remains unclear. The senescence-associated secretory phenotype (SASP) is composed of proteins released by senescent cells. We assessed the prognostic significance and biologic pathways associated with the SASP in human HF using a plasma proteomics approach. We measured 25 known SASP proteins among 2248 PHFS (Penn HF Study) participants using the SOMAScan V4 assay. We extracted the common variance in these proteins to generate SASP factor scores and assessed the relationship between these SASP factor scores and (1) all-cause death and (2) the composite of death or HF hospital admission. We also assessed the relationship of each SASP factor to 4746 other proteins, correcting for multiple comparisons, followed by pathway analyses. Two SASP factors were identified. Both factors were associated with older age, lower estimated glomerular filtration rate, and more advanced New York Heart Association class, among other clinical variables. Both SASP factors exhibited a significant positive association with the risk of death independent of the Meta-Analysis of Global-Group in Chronic HF score and NT-proBNP (N-terminal pro-B-type natriuretic peptide) levels. The 2 identified SASP factors were associated with 1201 and 1554 proteins, respectively, belonging to various pathways including the coagulation system, complement system, acute phase response signaling, and retinoid X receptor-related pathways that regulate cell metabolism. Increased SASP components are independently associated with adverse outcomes in HF. Biologic pathways associated with SASP are predominantly related to coagulation, inflammation, and cell metabolism.